Time Banking as a Process Reform for Enhancing Ease of Living in India: An Intersectional Strategy for Community-led Co-production - Atul Kriti; Bhabya; Vishakha (Indian Journal of Public Administration, 2026)
As India pursues the vision of ‘Viksit Bharat’ by 2047, reformers emphasise shifting from state-centred provision to community co-production of services. This article evaluates time banking—a non-monetary currency system using time as currency—as a ‘nuts-and-bolts’ process reform for enhancing ease of living. Time banking treats every person’s hour of labour as equal. Using Sanjeev Sanyal’s six-type process-reform framework and recent data from flagship schemes, the study shows that time banks can reduce administrative friction and increase public service capacity without incurring additional fiscal outlays. It proposes a hybrid digital–analogue model and introduces an intersectionality mapping tool to ensure that reciprocity networks actively counter historical caste and gender hierarchies. The tool treats power as traffic at an intersection, naming roads (identity axes) and vehicles (discriminatory mechanisms), so that each person’s contributions (e.g., a Dalit woman’s hour) are valued equally. This grounded, inclusive design could make the ‘social software’ of public services more responsive, supporting India’s infrastructure development with strengthened community resilience and equity.